Molecular tipping points in plant cell surface H+ homeostasis and signalling - Kaltra Xhelilaj; Anja Thoe Fuglsang; Julien Gronnier; Michael Palmgren (Quantitative Plant Biology)
Hydrogen, a deceptively simple element, plays crucial roles in regulating life on Earth. The concentration of hydrogen ions (H+) determines the pH of biological systems and dictates virtually all biochemical processes. The pH modulates the structure, physicochemical properties and function of most macromolecules. The plant cell surface is characterized by tremendous variations in apoplastic pH, serving as informative signals shaping plant development and its interaction with the environment. Here, we discuss the principles underlying cell surface H+ homeostasis, the molecular tipping points that regulate fast, controlled and informative changes in apoplastic pH, as well as open questions regarding the regulation of plasma membrane H+-ATPases.